1980
DOI: 10.1111/j.1365-2133.1980.tb07654.x
|View full text |Cite
|
Sign up to set email alerts
|

Do corticosteroids prevent post-herpetic neuralgia?

Abstract: Forty otherwise healthy patients over 50 years of age with early, severe painful herpes zoster were randomly allocated to two groups for treatment. Twenty patients received prednisolone 40 mg daily with gradual reduction over a period of 4 weeks, whilst the other twenty patients received carbamazepine 100 mg four times daily. Thirteen of the twenty patients (65%) in the carbamazepine treated group developed post-herpetic neuralgia lasting up to 2 years, whilst only three of the twenty prednisolone treated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
2
2

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(58 citation statements)
references
References 16 publications
0
54
2
2
Order By: Relevance
“…1,2 Thus, PHN is difficult to manage and, unfortunately, refractory to most forms of treatment modalities. It has been demonstrated that antiviral treatment, [3][4][5][6] cortcosteroids, 7,8 sympathetic and regional nerve blockade, 9,10 and a combination of these therapies 11,12 in the early stage of disease have preventive effects on PHN and reduce the duration of acute pain in HZ. Early therapeutic interventions with antiviral drags, particularly newly developed drugs, such as valacyclovir hydrochloride and famciclovir, allowed dramatic improvements of the skin lesions of HZ and reductions in the incidence of PHN.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Thus, PHN is difficult to manage and, unfortunately, refractory to most forms of treatment modalities. It has been demonstrated that antiviral treatment, [3][4][5][6] cortcosteroids, 7,8 sympathetic and regional nerve blockade, 9,10 and a combination of these therapies 11,12 in the early stage of disease have preventive effects on PHN and reduce the duration of acute pain in HZ. Early therapeutic interventions with antiviral drags, particularly newly developed drugs, such as valacyclovir hydrochloride and famciclovir, allowed dramatic improvements of the skin lesions of HZ and reductions in the incidence of PHN.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain may be associated with postinflammatory fibrosis in the root ganglion but appears to be perpetuated by central mechanisms. 15 There is a preferential destruction of the large myelinated afferent nerve fibres in this condition. 16 Postherpetic neuralgia supports the gate theory of pain.…”
Section: Underlying Mechanismmentioning
confidence: 98%
“…Often the patient will tolerate firm pressure on these areas but not a light touch. ' 15 Eaglestein also found that the incidence of postherpetic neuralgia decreased from 73% to 30% following the use of oral steroids.9 However, many doctors consider the risk of systemic viral dissemination following the use of steroids to be too great to justify their use,'8'20'2' particularly for those patients with already depressed immunity.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…[5][6][7] More recently, the number of physicians prescribing oral corticosteroids during the acute phase of herpes zoster outbreak has been reduced because of negative study results, 8 the lack of randomized controls, and the fear of dissemination of herpes zoster virus in immunocompromised hosts. The recent introduction of potent antiviral medications has shown some efficacy in reducing the frequency of postherpetic neuralgia.…”
Section: Commentmentioning
confidence: 99%